STRENGTHENING REPURCHASE INTENTION THROUGH PERCEIVED VALUE: EMPIRICAL EVIDENCE FROM JAKARTA’S ORGANIC FOOD CONSUMERS - Cindy Carysta; Tommy Setiawan Ruslim (International Journal of Application on Economics and Business, 2026)
This study examines how perceived value strengthens repurchase intention among organic food consumers in Jakarta. Using a quantitative approach, data were collected through an online questionnaire distributed to individuals who had previously purchased organic food products. A total of 233 valid responses were analyzed using Partial Least Squares Structural Equation Modeling. The findings indicate that perceived price and perceived quality positively influence perceived value, which in turn significantly enhances repurchase intention. Both direct and indirect effects were confirmed, highlighting the mediating role of perceived value in consumer decision-making. The model demonstrates moderate explanatory power, suggesting that consumers are more inclined to repurchase organic food when they perceive price fairness and consistent product quality that justify the value received. These results provide managerial insights for organic food businesses in designing pricing strategies and maintaining quality standards to encourage repeat purchases and long-term customer retention.